Key drivers of medical tourism in Malaysia / Suseela Devi Chandran ... [et al.] - Chandran, Suseela Devi; Puteh, Fadilah; Zianuddin, Azizan; Azmi, Nur Alia (Universiti Teknologi MARA Selangor and UiTM Press, 2018)
Globalization has transformed medical tourism into a booming revenue generating industry in many Southeast Asian (SEA) countries. One of the sub-sectors of tourism that contributed significantly towards their economic development was medical tourism. Medical tourism has attracted medical tourists from other parts of the world to the SEA region seeking medical attention and care. Among the SEA countries that are sought after for medical tourism in Malaysia. Medical tourism is rapidly expanding niche area and Malaysia has successfully claimed its position as one of the most preferred medical tourism destinations. The country has now emerged as the 3rd preferred medical tourism destination among SEA nations that offers competitive medical care and facilities. Thus, the objective of this paper is to examine the key drivers behind the impressive landscape of medical tourism development in Malaysia. This paper offers a discussion on the development of medical tourism in Malaysia based on the globalization theory that underpins this study. How globalization acts as a catalyst towards the development of medical tourism in Malaysia is also discussed in this paper.